Animals and human society (London ; New York)
1 online resource (xii, 199 pages)
Keywords: Modern society is beginning to re-examine its whole relationship with animals and the natural world. Until recently issues such as animal welfare and environmental protection were considered the domain of small, idealistic minorities. Now, these issues attract vast numbers of articulate supporters who collectively exercise considerable political muscle. Animals, both wild and domestic, form the primary focus of concern in this often acrimonious debate. Yet why do animals evoke such strong and contradictory emotions in people - and do our western attitudes have anything in common with those of other societies and cultures? Bringing together a range of contributions from distinguished experts in the field, Animals and Society explores the importance of animals in society from social, historical and cross-cultural perspectives.